ANALISIS EFEKTIVITAS PENERIMAAN DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA TOMOHON (PADA BADAN KEUANGAN DAERAH KOTA TOMOHON) - Rabunusa, Maya; Nangoi, Grace B.; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
Regional Tax is a compulsory contribution to the region owed by an individual or a coercive body under applicable law by not receiving direct remuneration and being used for regional purposes for the greatest welfare of the people. The purpose of this research is to know the effectiveness and contribution of hotel tax to Locally Generated Revenue in Tomohon City. In this study used the type of qualitative and quantitative data, for data sources using secondary data and analytical methods used are kualitative descriptive. Based on the research results, it is concluded that the level of hotel tax effectiveness of 2012 - 2016 is very effective. The year 2016 is the highest hotel tax effectiveness rate of 134.01%, while the lowest level of hotel tax effectiveness is in 2014 with a percentage of 27.40. Hotel tax contribution to Tomohon Locally Generated Revenue in 2012 - 2016 is good from year to year there is an increase although there is also a decrease. 2016 is the highest contribution of Hotel Tax to Locally Generated Revenue with percentage of 67.23% and the lowest is in 2015 with a percentage of 4.85% with an average contribution of 26,68%.Keywords: Effectiveness, Contributions, Hotel Tax, Local Revenue.